Intelligent robotics systems : inspiring the NEXT : Proceedings [of] 16th FIRA RoboWorld Congress, FIRA 2013, Kuala Lumpur, Malaysia, August 24-29, 2013 - FIRA Roboworld Congress 2013 : Kuala Lumpur, Malaysia).; Khairuddin Omar; Md Jan Nordin; Vadakkepat, Prahlad; Prabuwono, Anton Satria; Siti Norul Huda Sheikh Abdullah; Baltes, Jacky; Shamsudin Mohd Amin; Wan Zuha Wan Hassan; Mohammad Faidzul Nasrudin (Heidelberg, Germany : Springer, 2013)
This book constitutes the refereed proceedings of the 16th FIRA RoboWorld Congress, FIRA 2013, held in Kuala Lumpur, Malaysia, in August 2013. The congress consisted of the following three conferences: 5th International Conference on Advanced Humanoid Robotics Research (ICAHRR), 5th International Conference on Education and Entertainment Robotics (ICEER), and 4th International Robotics EducationForum (IREF). The 38 revised full papers presented were carefully reviewed and selected from 112 submissions. They cover various topics related to the technical developments and achievements in the field of robotics.
Book is accompanied by one computer optical disc bearing the same call number entitled'Intelligent robotics systems : inspiring the NEXT' and available at PL2.
Includes bibliographical references and index.
Keywords: Robotics -- Congresses